2008
DOI: 10.1598/jaal.52.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Reading Workshop: Beyond Books With New Literacies and Instructional Technologies

Abstract: In response to the challenge of meeting the needs of today's learners, teachers must know how to teach and facilitate new literacies and instructional technologies. This article introduces the concept of an electronic reading workshop (ERW), in which participants read eBooks, respond to literature in digital response journals, participate in online literature discussions, and create technology‐based literature extension projects. The article further explains how an ERW was introduced and implemented within a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 8 publications
1
22
0
2
Order By: Relevance
“…This finding supports the literature on learners' generative and interpretive capacities when they engage in multimodal responses to texts (Ballentine & Hill, 2000;Clyde, 2003;O'Brien, 2001;Short, Kauffman, Kahn, 2000;Whitin, 1996;2005;Wilhelm, 2008). In addition, the results support the value of the multimodal affordances of digital media for students' meaning making (Larson, 2008;O'Brien, 2001;Whitin, 2009). The use of digital media enabled symbol weaving in the group's deliberate layering of sound effects, text, music, voiceovers, layout, color, and other design elements for expanded and transformed meanings (Whitin, 2009).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This finding supports the literature on learners' generative and interpretive capacities when they engage in multimodal responses to texts (Ballentine & Hill, 2000;Clyde, 2003;O'Brien, 2001;Short, Kauffman, Kahn, 2000;Whitin, 1996;2005;Wilhelm, 2008). In addition, the results support the value of the multimodal affordances of digital media for students' meaning making (Larson, 2008;O'Brien, 2001;Whitin, 2009). The use of digital media enabled symbol weaving in the group's deliberate layering of sound effects, text, music, voiceovers, layout, color, and other design elements for expanded and transformed meanings (Whitin, 2009).…”
Section: Discussionmentioning
confidence: 54%
“…All these researchers' findings bolstered my commitment to using multiple modes, including the multimedia of digital technology, for my students' responses to challenging literature. Larson (2008) reported on a conceptual framework that she called Electronic Reading Workshop (ERW), based on the framework of reading workshop, for her pre-service undergraduate students. ERW enabled opportunities for new literacy practices and integration of technology.…”
Section: Multimodal Reader Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Também há estudos como os de Larson (2008), que investigaram o uso de tecnologias digitais para ambientes de ensino, revelando por meio de um experimento com futuros professores, que a expectativa dos participantes passou de desfavorável para favorável, embora ainda preferissem o método impresso de leitura. A autora considera que a experiência com os futuros professores possibilitaria novas oportunidades de interação dos estudantes com a tecnologia, sendo para ela imperativa a nova alfabetização orquestrada pelos professores.…”
Section: Sobre Dispositivos E-readerunclassified
“…It stands to reason that if my English scholars have positive experiences as students in courses that effectively utilize technology, they are likely to effectively implement these strategies in their own teaching. Indeed, Larson's (2008) research found that, "Embedding technology in literacy methods courses is an effective factor in preparing tomorrow's teachers to weave technology into their lesson plans and, consequently, [positively] affect K-12 students during field experiences and in future classrooms" (p. 121).…”
Section: Theoretical Frameworkmentioning
confidence: 99%